Diagnóstico sobre a contratação de profissionais em engenharia civil na cidade de Mossoró/RN - Guimarães, Diego de Sousa (Universidade Federal Rural do Semi-Árido, 2021)
When entering the job market, civil engineering professionals do not always understand how the dynamics of contracting their services work, the most demanded works and especially what is the profile expected by the contractors. Therefore, understanding how the job market works before being inserted in it is an important tool to help new professionals in the field in the search for ways to adapt to this new phase of their lives. In this context, the present work had as a general objective, researching the hiring of a civil engineering professional for construction and/or reform services by the population of Mossoró. The research was carried out with data collection from a system of self-interviews carried out through an online questionnaire, for a defined sample with statistical basis. The results were identified from the descriptive statistical analysis for data referring to the spatial and economic characterization of the interviewees; diagnosis of the carrying out of renovation and/or construction works, among others. Use the Chi-square test with the analysis of standardized residuals and a significance level of 1%, through the R software, in the association between responses to the questionnaire. An analysis of the results indicated an association between the interviewees' economic class and carrying out renovation and/or construction (p<0.0001). The percentage of respondents who built and/or renovated was verified, it was possible to verify that 26% hired the services of a professional in civil engineering. There was an association of economic class and the hiring of a civil engineering professional (p <0.0001), with classes A and B having a higher rate of professionals hired with an emphasis on class B. In general, the work performed provided an overview of the hiring of professional in civil engineering for construction and / or reform services by the population of Mossoró, which may be of interest to these professionals
Keywords: Engenheiro civil; Atribuição profissional; Característica do profissional em engenharia; Mercado de trabalho; Civil engineer; Professional attribution; Characteristics of the engineering professional; Job market; ENGENHARIAS::ENGENHARIA CIVIL